Etnomathematics In E-Modules Using A Scientific Learning Approach For JHS Students - Faisyal, Intan Dyra Shari; Supriadi, Nanang; Pratiwi, Dona Dinda (Mathline : Jurnal Matematika dan Pendidikan Matematika, 2023)
This study has the aim of obtaining a suitable e-mathematical module, valid and interesting, and effective for use in learning. The research method used is development research or R&D (Research and Development) through the ADDIE approach (Analysis, Design, Development, Implementation, and Evaluation) with the subject of State Junior High School (Junior High School) students in Bandar Lampung City. The instruments used are interviews, questionnaires (questionnaires) in the form of expert validation questionnaires, needs analysis, and product trials to students, as well as documentation. The results of the study based on the validation of material and media experts obtained scores of 3.55 and 3.43 with the criteria "fit for use". The results of the product attractiveness trial to students for large groups and small groups obtained scores of 3.71 and 3.73 on the "very interesting" criteria. The effectiveness test of the N-gain score obtained a result of 0.71 which was classified in the "high" category.